Effects of plyometric, SAQ and traditional training on sprint, agility, jumping passing and shooting performance in young soccer players - McDermott, Shane (2016)
McDermott, Shane 2016. Effects of Plyometric, SAQ and traditional training on sprint, agility, jumping passing and shooting performance in young soccer players. Department of Biology of Physical Activity. University of Jyväskylä. Master’s Thesis in Science of Sports Coaching and Fitness Testing. 57 pp. The purpose of this study was to perform an 8-week intervention program in order to provide a recommendation of the most suitable training program for young soccer players for improving sprint performance, agility and jumping parameters (strength and power). The participants used in this project were boys aged between 14-16 years old from Jyväskylän Komeetat Ry (soccer club in Jyvaskyla). 33 players in total took part in the study. The following subject information was recorded; age (years), weight (kg), height (cm), circumference of the thigh (cm) and years of training. The different groups included; a speed, agility and quickness group (SAQ, n= 11), plyometric group (PG, n=12), and control group (CG, n=10). Players were randomly assigned into each group according to their Pre-test results in the 30meter sprint, Agility and multiple 5 bound (MB5) test. The 2 experimental groups had 2 sessions per week lasting 30-45 minutes per session. At the same time players in the control group continued with traditional soccer training. During each testing period the following measurements were taken in the laboratory; Isometric leg press and Countermovement jump (CMJ). The Multiple 5 Bounds (MB5) Test) and the 30meter sprint with 10m acceleration phase were measured on a running track. The Finish FA agility tests (without the ball), passing test and shooting test took place on soccer pitch. The SAQ group significantly improved their absolute and relative strength levels in the isometric leg press (p<0.001) from pre to post. The Plyometric Group were the only group to significantly improve their performance in the MB5 (p<0.05) from pre to post. The control group significantly improved their performance in the CMJ (p<0.05), however they were the only group to get significantly slower in the 30m Sprint (p<0.05) post measurements. The hypothesis for this study was that the plyometric group and SAQ group will achieve better improvements in performance compared to the control group that performed traditional soccer training. It is satisfactory to have two substituted sessions if the aim is to produce improvements in sprinting performance.